2001
DOI: 10.1053/jlts.2001.22450
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytokine gene polymorphisms in acute rejection and renal impairment after liver transplantation

Abstract: Although immunosuppressive regimens are effective, rejection occurs in up to 50% of patients after orthotopic liver transplantation (OLT), and there is concern about side effects from long-term therapy. Knowledge of clinical and immunogenetic variables may allow tailoring of immunosuppressive therapy to patients according to their potential risks. We studied the association between transforming growth factor-␤, interleukin-10, and tumor necrosis factor ␣ (TNF-␣) gene polymorphisms and graft rejection and renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 35 publications
0
27
1
Order By: Relevance
“…In fact, in neither renal nor liver transplant patients was an association between TNF producer genotype and rejection found at the mRNA level (45). In addition, GM-CSF, the TNF-reconstituting agent in our model, has been safely applied following liver transplantation in the treatment of neutropenia (44).…”
Section: Discussionmentioning
confidence: 78%
“…In fact, in neither renal nor liver transplant patients was an association between TNF producer genotype and rejection found at the mRNA level (45). In addition, GM-CSF, the TNF-reconstituting agent in our model, has been safely applied following liver transplantation in the treatment of neutropenia (44).…”
Section: Discussionmentioning
confidence: 78%
“…In a recent study of 121 white OLT recipients, Jonsson et al 21 found that recipient cytokine genotypes did not have a major role in graft rejection or renal impairment. Evans et al 22 found that the observed association between the high TNF-␣ producing allele and chronic rejection in 89 liver transplant recipients was caused by linkage to HLA-DR3.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies that have looked at outcome of disease have found no association with TNF SNPs. 104,[111][112][113][114][115] However, two studies have appeared that did find an association of TNF SNPs with HCV. 116,117 The latter study 117 is curious not because of the reported higher occurrence of the À238A allele among chronic HCV patients, but because the reported frequency in a healthy control group (n ¼ 99) drops from 7 117 to 3.5% in an article published concurrently by the same group.…”
Section: Leprosymentioning
confidence: 99%